Supply chain risk management : understanding emerging threats to global supply chains - Manners-Bell, John (London, United Kingdom : New York, NY Kogan Page Limited, 2018)
With increased outsourcing, globalisation, and just-in-time production, the ability to effectively identify, assess and manage risks in the supply chain is more important than ever. Supply Chain Risk Management is a practical learning resource which explores a wide range of external threats to the supply chain such as natural disasters, economic risk, terrorism and piracy. An ideal companion to academic and professional training courses, it presents a robust set of strategies which can minimise and mitigate supply chain risk. Supply Chain Risk Management includes numerous best practice case studies, with each case documenting the company's supply chain or production strategy and outlining the catastrophic event which occurred. This comprehensive second instalment of Supply Chain Risk, which won the 2014 ACA-Bruel Special Mention prize, analyses the supply chain consequences, material losses, management response, and resultant changes to a company's supply chain strategy. With a new chapter on cyber threats to supply chains, Supply Chain Risk Management also includes academic pedagogy such as objectives, summaries and a key point checklist in each chapter.
Includes bibliographical references and index.
oif 21/01/2020
Loans
Keywords: Business logistics; Materials management; Risk management